2022
DOI: 10.1088/1755-1315/1070/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical surveys as a tool for geotechnical monitoring of disturbed land reclamation

Abstract: The article is devoted to the issues of controlling the reclamation of disturbed lands after the end of field development. It is proved that duration of transformation processes of the geological environment after a mine recultivation stage determines the necessity of control of the changes including the ones carried out by means of geophysical investigations. The way methods of engineering geophysics increase reliability of information about the state of stability of recultivated areas by the example of slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The integration of seismic and electrical methods proved sufficient for mapping the carbonates and schist tectonic contact at the Mavropigi open pit mine. The present work provides the geophysical results related to the sustainability of lands with the scope to avoid their misuse and to increase geotechnical safety [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The integration of seismic and electrical methods proved sufficient for mapping the carbonates and schist tectonic contact at the Mavropigi open pit mine. The present work provides the geophysical results related to the sustainability of lands with the scope to avoid their misuse and to increase geotechnical safety [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the combination of geophysical techniques sensitive to different physical properties can reveal subsurface structures like tectonic contacts, which is not always the case when using the classic engineering geological methods [1]. The seismic reflection method proved useful for a shallow depth of investigation [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations